2009
DOI: 10.1002/lt.21796
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of autoimmune hepatitis after liver transplantation

Abstract: Autoimmune hepatitis has been reported to recur after liver transplantation. The aim of our study was to evaluate the risk factors associated with recurrence of autoimmune hepatitis. Forty-six patients that underwent liver transplantation because of end-stage liver disease secondary to autoimmune hepatitis were studied. Recurrence of autoimmune hepatitis was diagnosed in 11 of the 46 (24%) patients, and the overall 5-year probability of recurrence was 18%. By univariate Cox analysis, the features before liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 34 publications
3
128
0
6
Order By: Relevance
“…However, since the relapse rate and the rate of immunosuppressant use were significantly higher in the patients who developed cirrhosis during the follow-up period than in non-cirrhosis patients, it seems that many patients who exhibited relapse from steroid resistance developed cirrhosis. It has been reported that a high IgG level before relapse and a long period to remission are risk factors for relapse (5,19). Regarding the use of immunosuppressants, it appears that the rate of immunosuppressant use was high in this study because many of the cases of relapse were caused by steroid resistance.…”
Section: Discussionmentioning
confidence: 53%
“…However, since the relapse rate and the rate of immunosuppressant use were significantly higher in the patients who developed cirrhosis during the follow-up period than in non-cirrhosis patients, it seems that many patients who exhibited relapse from steroid resistance developed cirrhosis. It has been reported that a high IgG level before relapse and a long period to remission are risk factors for relapse (5,19). Regarding the use of immunosuppressants, it appears that the rate of immunosuppressant use was high in this study because many of the cases of relapse were caused by steroid resistance.…”
Section: Discussionmentioning
confidence: 53%
“…The severity of the original liver disease may also be a factor in disease recurrence after liver transplantation. Patients with recurrent AIH have higher serum levels of immunoglobulin G and histological findings of plasma cell infiltration and severe inflammatory activity more often immediately prior to transplantation than patients without recurrence (Montano-Loza et al, 2009). These observations suggest that recurrent AIH is a continuum of the original disease or a newly created process in a susceptible host with a propensity for severe immune reactivity (Czaja, 2009).…”
Section: Components Of Thementioning
confidence: 99%
“…These observations suggest that recurrent AIH is a continuum of the original disease or a newly created process in a susceptible host with a propensity for severe immune reactivity (Czaja, 2009). They imply that aggressive disease suppression immediately prior to transplantation might alter the consequences after transplantation (Montano-Loza et al, 2009) or that an vulnerable individual may be identified early who warrants close surveillance after transplantation (Czaja, 2009). Most likely, the intrinsic bases for recurrent AIH interact with the extrinsic factors to define the true risk.…”
Section: Components Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…10,[146][147][148] The implementation of a new nonstandard therapy should not delay or supersede the decision to proceed with liver transplantation in the appropriate candidate. …”
mentioning
confidence: 99%